Utilization of Palm Kernell Shells and Palm Oil Sludge as Raw Materials of Biobriquette Charcoal - Muhammad Ginta Munthe; Achwil Putra Munir; Adian Rindang (Universitas Sumatera Utara, 2015)
Briquette is one type of alternative fuel made ​​from various kinds of biomass. Biomass used in this study was the palm kernel shells and palm oil sludge. This research was aimed to make biobriquette charcoal from palm kernel shells and palm oil waste sludge as an alternative fuel and to test the quality of biobriquette charcoal. Testing was performed under non factorial completely randomized design. The parameters observed were calorific value, water content, density and ash content. The results of this study indicated that the composition of biobriquette charcoal affected the calorific value, water content, density and ash content. The average of calorific value was 3714.16 cal/g, the average of water content was 7.95 %, the average of density was 0.79 (g / cm3) the average ash content was 19.84 (%). Keywords : Briquette , palm kernel shells ,sludge, waste